Interação entre os atores : o caso serra gaúcha a partir do modelo da tríplice hélice - Marchi, Felipe Luis de (My University, 2015)
This dissertation aimed to analyze the mechanisms and structures for the promotion to innovation disposed by University of Caxias do Sul, starting from the theoretical model of the Triple Helix. The research involved the identification of the interactions between the University, the instruments and innovation polices of the Secretary of Science, Innovation and Technological Development of the Government of the State of Rio Grande do Sul and the activities applied to innovation of the company Keko Acessórios S.A.. In this context were characterized the activities and innovation policies of the three agents considering their interactions with external agents, aiming to realize the interactions between them. Using a qualitative approach, this exploratory study employed semi-structured interviews with a script. The method of discourse analysis was used and carried out with Atlas.TI software ®, version 7. The results show an assiduous participation of agents in search of interactions with external agents, through resources, knowledge and analysis of the market for the realization of their goals, activities and innovation policies. This search is evident when it comes to the achievement of individual objectives, making the interaction with external agents a consequence of this process, limiting external participation in innovation activities.
Esta dissertação objetivou analisar os mecanismos e estruturas de promoção à inovação dispostos pela Universidade de Caxias do Sul, a partir do modelo teórico da Tríplice Hélice. A pesquisa envolveu a identificação das interações da universidade com os instrumentos e políticas de inovação da Secretaria da Ciência, Inovação e Desenvolvimento Tecnológico do Governo do Estado do Rio Grande do Sul e com o as atividades aplicadas à inovação da empresa Keko Acessórios S.A. Neste contexto foram caracterizadas as atividades e políticas de inovação dos três agentes considerando suas interações com agentes externos, visando pontuar as interações entre eles. Com abordagem qualitativa, o estudo exploratório empregou entrevistas com roteiro semiestruturado. Utilizou-se o método de análise de discurso, através do software ATLAS.ti®, versão 7. Os resultados apresentam uma participação assídua dos agentes na busca de interações com agentes externos, através de recursos, conhecimento e análise de mercado, para a realização de seus objetivos, dentro das atividades e políticas de inovação. Essa busca fica evidente quando se trata da realização dos objetivos individuais, fazendo com que a interação com os agentes externos seja uma consequência desse processo, limitando a participação externa nas atividades de inovação.
Keywords: Universidades e faculdades - Inovações tecnológicas; Administração - Inovações tecnológicas; Universities and colleges - Technological innovations; Management - Technological innovations -